2014
DOI: 10.1007/s11325-014-1026-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of continuous positive airway pressure treatment on myocardial performance in patients with obstructive sleep apnea. A conventional and tissue Doppler echocardiographic study

Abstract: CPAP therapy in OSA patients was found to improve right heart chambers remodeling and performance as well as somatometric characteristics. The impact of CPAP on LV performance seems less pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Although the trans-tricuspid gradient did not show improvement at follow up, it was slightly reduced when compared to baseline values in the CPAP group. There are several studies which confirm these findings [55][56][57].Karamanzanis et colleagues [58] showed partially similar results, the differences between the findings consisting of the effect of CPAP on RV diameter and LVEF, parameters which did not improve through our follow up period. In an observational study [59], the group showed that 6 months of CPAP therapy improved pulmonary hypertension in OSA patients, these results being in accordance with other studies [60].…”
Section: Effect On Ventricular Functionsupporting
confidence: 75%
“…Although the trans-tricuspid gradient did not show improvement at follow up, it was slightly reduced when compared to baseline values in the CPAP group. There are several studies which confirm these findings [55][56][57].Karamanzanis et colleagues [58] showed partially similar results, the differences between the findings consisting of the effect of CPAP on RV diameter and LVEF, parameters which did not improve through our follow up period. In an observational study [59], the group showed that 6 months of CPAP therapy improved pulmonary hypertension in OSA patients, these results being in accordance with other studies [60].…”
Section: Effect On Ventricular Functionsupporting
confidence: 75%
“…Similar findings on the right ventricular size and function were obtained in a very recent uncontrolled study among 44 patients with moderate or severe OSA following 12 months of CPAP. 82 …”
Section: The Cardiovascular System In Osamentioning
confidence: 99%
“…
We appreciate the interest of A.M. Esquinas and R. PerezRojo regarding our manuscript [1] relevant to the impact of continuous positive airway pressure (CPAP) treatment on myocardial performance, in patients with obstructive sleep apnea (OSA).We agree that beyond OSA, various factors and associated comorbidities may affect left-and right-sided myocardial performance [2]. Nevertheless, in our study, we selected a cohort of patients with a little comorbidity as possible in order to focus on the net effect of CPAP treatment on OSA patients and to exclude possible confounders.
…”
mentioning
confidence: 93%
“…We appreciate the interest of A.M. Esquinas and R. PerezRojo regarding our manuscript [1] relevant to the impact of continuous positive airway pressure (CPAP) treatment on myocardial performance, in patients with obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%